High tensile strength glass wool and method of making same
Patent Information
- Application Number
- CN202611037099.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]目前常规玻璃棉所用粘结剂体系存在明显技术缺陷,导致制品普遍存在抗拉强度不足的问题,制约了其高端工况应用
[0017]与现有技术相比,本发明提供了一种高抗拉强度玻璃棉,采用环氧树脂作为基体粘结剂,并引入丙烯腈-苯乙烯-丙烯酸酯三元共聚物粉末与聚砜纤维复配改性,通过两组分协同作用,有效解决了传统玻璃棉抗拉强度低、易分层断裂的技术缺陷,显著提升了制品整体力学稳定性。其中,丙烯腈-苯乙烯-丙烯酸酯三元共聚物粉末可均匀掺杂于环氧树脂胶层内部,改善纯环氧树脂固化后胶膜脆性大的问题,优化粘结剂内部交联结构,缓解拉伸受力时的应力集中现象,避免胶膜开裂、纤维脱粘,同时,聚砜纤维可在玻璃棉内部形成交错穿插的辅助补强骨架,与玻璃纤维棉、改性环氧树脂粘结体系形成复合网络结构,承接并分散外部拉伸载荷。二者协同互补,既强化了树脂与玻璃纤维的界面结合强度,又通过纤维骨架提升了整体抗拉伸形变能力。相较于传统玻璃棉,大幅提升了制品的抗拉性能。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass wool technology, specifically to a high tensile strength glass wool and its preparation method. Background Technology
[0002] Glass wool is an inorganic porous thermal insulation material made with glass fiber as the matrix. With its advantages such as low thermal conductivity, sound absorption, flame retardancy, corrosion resistance, lightweight, and environmental friendliness, it is widely used in building HVAC, industrial pipelines, rail transportation, and power equipment, and is currently a mainstream thermal insulation and energy-saving material. The molding and structural shaping of existing industrialized glass wool products rely entirely on the high-temperature curing and cross-linking of adhesives to form a film, bonding and fixing the discrete glass fibers. The bonding effect of the adhesive directly determines the structural stability and mechanical properties of the product.
[0003] The adhesive systems used in conventional glass wool currently have significant technical defects, resulting in insufficient tensile strength in the products and hindering their application in high-end applications. Existing adhesives produce brittle and poorly tough films after curing, only achieving point-to-point bonding between fibers and failing to form a continuous, uniform, flexible adhesive network. Furthermore, the thin diameter and soft texture of glass fibers result in weak interfacial bonding between the fibers and the adhesive. When the product is subjected to tensile forces, stress concentration easily occurs at the bonding points, leading to film cracking, fiber detachment, and an inability to effectively disperse and transfer stress, ultimately causing delamination and breakage of the product.
[0004] Furthermore, to ensure the fluffy insulation performance of glass wool and control production costs, the industry generally adopts a low-adhesion process. This makes it difficult for the adhesive to fully impregnate the interwoven fiber joints, resulting in poor internal bonding uniformity and significantly reducing the overall tensile strength. In actual construction and long-term use, glass wool is prone to damage and detachment due to hoisting tension, equipment vibration, and alternating stress. This not only increases construction losses and maintenance costs but also damages the integrity of the insulation and noise reduction structure, affecting the operational stability of equipment and building envelopes.
[0005] In summary, glass wool prepared by existing adhesive molding processes has poor mechanical stability and insufficient tensile strength, making it difficult to meet the demanding requirements of special buildings, high-end industrial equipment, and other applications. Summary of the Invention
[0006] To address the above technical problems, this invention provides a high tensile strength glass wool and its preparation method. The glass wool provided by this invention improves the tensile strength of the glass wool by modifying the composition of the binder.
[0007] The specific technical solution of the present invention is as follows: According to one aspect of the present invention, a high tensile strength glass wool is provided, comprising glass fiber wool and an adhesive, wherein the adhesive comprises the following raw materials in parts by weight: 40-45 parts epoxy resin, 4-6 parts acrylonitrile-styrene-acrylate terpolymer, 5-12 parts polysulfone fiber, 4-8 parts curing agent, 1-3 parts diluent, and 0.5-0.8 parts silane coupling agent.
[0008] In the above technical solution, the acrylonitrile-styrene-acrylate terpolymer includes at least one of XC280G, PW-957, S210B and WX-9951UV.
[0009] In the above technical solution, the polysulfone fiber has an average diameter of 200~300nm and an average length of 1~2mm.
[0010] In the above technical solution, the method for preparing polysulfone fiber includes the following steps: dissolving polysulfone in a solvent to obtain a solution; and using the solution as a spinning solution to obtain the polysulfone fiber through electrospinning.
[0011] In the above technical solution, the preparation method of the polysulfone fiber includes the following steps: dissolving polysulfone in a solvent to obtain a solution; adding nano-zirconia to the solution and dispersing it evenly to obtain a dispersion; and using the dispersion as a spinning solution to obtain the polysulfone fiber through electrospinning.
[0012] In the above technical solution, the mass-to-volume ratio of polysulfone to solvent is 1g:6~12mL.
[0013] In the above technical solution, the voltage of electrospinning is 10~14kV, the receiving distance is 10~15cm, and the flow rate of the spinning solution is 0.15~0.30mL / h.
[0014] In the above technical solution, the mass of the nano-zirconia is 5% to 8% of the mass of the polysulfone.
[0015] In the above technical solution, the mass of the adhesive is 6% to 10% of the mass of the glass fiber cotton.
[0016] According to another aspect of the present invention, the present invention also provides a method for preparing the above-mentioned high tensile strength glass wool, comprising the following steps: Epoxy resin, acrylonitrile-styrene-acrylate terpolymer, polysulfone fiber and diluent are stirred and mixed, curing agent is added and mixed, and the mixture is sprayed onto glass fiber wool and cured to obtain the high tensile strength glass wool.
[0017] Compared with existing technologies, this invention provides a high-tensile-strength glass wool, using epoxy resin as the matrix binder and incorporating acrylonitrile-styrene-acrylate terpolymer powder and polysulfone fiber for modification. Through the synergistic effect of the two components, the technical defects of traditional glass wool, such as low tensile strength and easy delamination and breakage, are effectively solved, significantly improving the overall mechanical stability of the product. Specifically, the acrylonitrile-styrene-acrylate terpolymer powder can be uniformly incorporated into the epoxy resin adhesive layer, improving the brittleness of the cured epoxy film, optimizing the internal cross-linking structure of the binder, alleviating stress concentration under tensile stress, and preventing film cracking and fiber debonding. Simultaneously, the polysulfone fiber can form an interwoven auxiliary reinforcing skeleton within the glass wool, forming a composite network structure with the glass fiber wool and modified epoxy resin bonding system, bearing and dispersing external tensile loads. The two components work synergistically and complementaryly, strengthening the interfacial bonding strength between the resin and glass fiber, and improving the overall tensile deformation resistance through the fiber skeleton. Compared with traditional glass wool, the tensile performance of the product is significantly improved. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of this invention more apparent, the invention is described in detail below. It should be understood that the invention is not limited to the description herein.
[0019] Acrylonitrile-styrene-acrylate terpolymer The acrylonitrile-styrene-acrylate terpolymer used in this invention includes at least one of XC280G, PW-957, S210B, and WX-9951UV. In this invention, when the acrylonitrile-styrene-acrylate terpolymer is PW-957, it has a better effect on improving the tensile strength of glass wool compared to other types of materials.
[0020] Polysulfone fiber The polysulfone fiber used in this invention is obtained by electrospinning. The average diameter of the polysulfone fiber is 200~300nm, for example, it can be 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, etc.; the average length is 1~2mm, for example, it can be 1mm, 1.2mm, 1.4mm, 1.6mm, 1.8mm, 2mm, etc.
[0021] curing agent The curing agent used in this invention is a component known in the art that can be used as a binder in glass wool. As an example, the curing agent used in this invention can be m-phenylenediamine, dicyandiamide, etc. The curing agent can undergo a cross-linking reaction with epoxy resin to generate a tough cured product, enhancing the bonding force between glass fibers and ensuring the overall performance of the glass wool product; and it cures the epoxy resin under medium-temperature conditions, forming a cured product with high thermal stability and mechanical properties, ensuring that the glass wool can maintain good bonding effect and physical properties even at higher temperatures.
[0022] diluent The diluent used in this invention is a component known in the art for use in adhesives for glass wool. As an example, acetone can be used as the diluent in this invention. Acetone, as a diluent, reduces the viscosity of the epoxy resin adhesive, making it easier for it to penetrate and disperse evenly between the glass wool fibers during glass wool production. This helps increase the contact area between the adhesive and the glass wool fibers, enhancing the bonding effect, and also improves the workability, making the adhesive application smoother during spraying and reducing problems such as uneven application and nozzle clogging caused by high viscosity, thereby improving the quality stability and production efficiency of glass wool products. In addition, ethanol, n-butanol, toluene, xylene, etc., can also be used as diluents for epoxy resin adhesives in glass wool applications.
[0023] High tensile strength glass wool The high tensile strength glass wool component of the present invention includes glass fiber wool and binder.
[0024] In high tensile strength glass wool, the mass of the binder is 6% to 10% of the mass of the glass fiber wool.
[0025] In high tensile strength glass wool, the binder includes the following components: epoxy resin, acrylonitrile-styrene-acrylate terpolymer, polysulfone fiber, curing agent and diluent, and silane coupling agent.
[0026] In the adhesive for high tensile strength glass wool, the epoxy resin is in the amount of 40-45 parts by weight, preferably 41-44 parts, and more preferably 42-43 parts. The acrylonitrile-styrene-acrylate terpolymer has a weight ratio of 4 to 6 parts, preferably 4.5 to 5.5 parts, and more preferably 4.8 to 5.2 parts.
[0027] The polysulfone fiber is 5 to 12 parts by weight, preferably 6 to 11 parts, and more preferably 7 to 10 parts; The curing agent is present in 4 to 8 parts by weight, preferably 5 to 7 parts, and more preferably 5.5 to 6.5 parts; The diluent is 1 to 3 parts by weight, preferably 1.5 to 2.5 parts, more preferably 1.8 to 2.2 parts; the silane coupling agent is 0.5 to 0.8 parts.
[0028] In the binder of high tensile strength glass wool, the preparation method of the above-mentioned polysulfone fiber can refer to the following method one: dissolve polysulfone in a solvent to obtain a solution; use the solution as a spinning solution to obtain polysulfone fiber through electrospinning.
[0029] Alternatively, you can refer to the following method two: Dissolve polysulfone in a solvent to obtain a solution; add nano-zirconia to the solution and disperse it evenly to obtain a dispersion; use the dispersion as a spinning solution to obtain polysulfone fibers through electrospinning.
[0030] In methods one and two above, the mass-to-volume ratio of polysulfone to solvent is 1g:6~12mL, preferably 1g:7~11mL, and more preferably 1g:8~10mL. This ensures that the polysulfone is fully dissolved in the solvent, forming a uniform spinning solution suitable for electrospinning. The electrospinning voltage is 10~14kV, preferably 11~13kV, and more preferably 11.5~12.5kV. Within this voltage range, sufficient electric field force can be provided to the spinning solution to overcome its surface tension, allowing the spinning solution to be stretched and refined under the action of the electric field to form fibers. The receiving distance is 10~15cm, preferably 11~14cm, and more preferably 12~13cm. A suitable receiving distance helps the fibers to fully evaporate the solvent during the preparation process, forming a good morphology and ensuring that the fibers can be uniformly collected on the receiving device. If the distance is too short, the solvent will not evaporate sufficiently, and the fibers will easily stick together; if the distance is too long, the fibers may be unevenly dispersed due to instability during flight. The flow rate of the spinning solution is 0.15~0.30 mL / h, preferably 0.18~0.27 mL / h, and more preferably 0.20~0.25 mL / h. This flow rate range ensures the continuity and stability of the spinning process.
[0031] In Method 2 above, nano-zirconia particles are introduced during spinning for in-situ modification. Compared with pure polysulfone fibers and conventional inorganic nano-modified fillers such as silica and talc, nano-zirconia has higher surface activity and structural adaptability. It can be uniformly dispersed in the polysulfone fiber matrix, effectively filling the micropores and structural defects inside the fiber. After improving the bulk strength of a single polysulfone fiber, it works synergistically with the copolymer to further bear and disperse external tensile loads, thereby further improving the tensile strength of the glass wool. The mass of nano-zirconia is 5% to 8% of the mass of polysulfone.
[0032] Preparation method of high tensile strength glass wool The present invention also provides a method for preparing high tensile strength glass wool as described above, comprising: Epoxy resin, acrylonitrile-styrene-acrylate terpolymer, polysulfone fiber and diluent are stirred and mixed, curing agent is added and mixed, and the mixture is sprayed onto glass fiber wool and cured to obtain the high tensile strength glass wool.
[0033] To further illustrate the present invention, detailed descriptions will be provided below through the following embodiments. The raw materials used in the following embodiments and comparative examples of the present invention are all commercially available products. Specifically, the acrylonitrile-styrene-acrylate terpolymer consists of particles with an average particle size of 325 mesh, the polysulfone resin is type P-3703, and the silane coupling agent is type KH560.
[0034] Example 1 The preparation method of high tensile strength glass wool includes the following steps: Polysulfone was dissolved in a mixed solvent of N,N-dimethylacetamide and acetone (volume ratio of N,N-dimethylacetamide and acetone was 7:3) to obtain a solution. The solution was used as a spinning solution, and electrospinning was performed at a flow rate of 0.15 mL / h, a voltage of 14 kV and a receiving distance of 15 cm to obtain polysulfone fibers with an average diameter of 300 nm and an average length of 2 mm. By weight, 45 parts of epoxy resin (model E-51), 6 parts of acrylonitrile-styrene-acrylate terpolymer (model XC280G), 12 parts of polysulfone fiber, 0.7 parts of silane coupling agent, and 3 parts of acetone were mixed and stirred. 8 parts of m-phenylenediamine were added and mixed. The mixture was then sprayed onto glass fiber wool and cured at 80°C for 2 hours, followed by curing at 150°C for 2 hours to obtain high tensile strength glass wool (the mass of the adhesive is 6% of the mass of the glass fiber wool).
[0035] Example 2 The preparation method of high tensile strength glass wool includes the following steps: Polysulfone was dissolved in a mixed solvent of N,N-dimethylacetamide and acetone (volume ratio of N,N-dimethylacetamide and acetone was 7:3) to obtain a solution. The solution was used as a spinning solution, and electrospinning was performed at a flow rate of 0.30 mL / h, a voltage of 10 kV and a receiving distance of 10 cm to obtain polysulfone fibers with an average diameter of 200 nm and an average length of 1 mm. By weight, 40 parts of epoxy resin (model E-51), 4 parts of acrylonitrile-styrene-acrylate terpolymer (model XC280G), 5 parts of polysulfone fiber, 0.7 parts of silane coupling agent, and 1 part of acetone were mixed and stirred. 4 parts of m-phenylenediamine were added and mixed. The mixture was then sprayed onto glass fiber wool and cured at 80°C for 2 hours, followed by curing at 150°C for 2 hours to obtain high tensile strength glass wool (the mass of the adhesive is 10% of the mass of the glass fiber wool).
[0036] Example 3 The preparation method of high tensile strength glass wool includes the following steps: Polysulfone was dissolved in a mixed solvent of N,N-dimethylacetamide and acetone (volume ratio of N,N-dimethylacetamide and acetone was 7:3) to obtain a solution. The solution was used as a spinning solution, and electrospinning was performed at a flow rate of 0.15 mL / h, a voltage of 14 kV and a receiving distance of 15 cm to obtain polysulfone fibers with an average diameter of 300 nm and an average length of 2 mm. By weight, 45 parts of epoxy resin (model E-51), 6 parts of acrylonitrile-styrene-acrylate terpolymer (model S210B), 12 parts of polysulfone fiber, 0.7 parts of silane coupling agent, and 3 parts of acetone were mixed and stirred. 8 parts of m-phenylenediamine were added and mixed. The mixture was then sprayed onto glass fiber wool and cured at 80°C for 2 hours, followed by curing at 150°C for 2 hours to obtain high tensile strength glass wool (the mass of the adhesive is 6% of the mass of the glass fiber wool).
[0037] Example 4 The preparation method of high tensile strength glass wool includes the following steps: Polysulfone was dissolved in a mixed solvent of N,N-dimethylacetamide and acetone (volume ratio of N,N-dimethylacetamide and acetone was 7:3) to obtain a solution. The solution was used as a spinning solution, and electrospinning was performed at a flow rate of 0.15 mL / h, a voltage of 14 kV and a receiving distance of 15 cm to obtain polysulfone fibers with an average diameter of 300 nm and an average length of 2 mm. By weight, 45 parts of epoxy resin (model E-51), 6 parts of acrylonitrile-styrene-acrylate terpolymer (model WX-9951UV), 12 parts of polysulfone fiber, 0.7 parts of silane coupling agent, and 3 parts of acetone were mixed and stirred. 8 parts of m-phenylenediamine were added and mixed. The mixture was then sprayed onto glass fiber wool and cured at 80°C for 2 hours, followed by curing at 150°C for 2 hours to obtain high tensile strength glass wool (the mass of the adhesive is 6% of the mass of the glass fiber wool).
[0038] Example 5 The preparation method of high tensile strength glass wool includes the following steps: Polysulfone was dissolved in a mixed solvent of N,N-dimethylacetamide and acetone (volume ratio of N,N-dimethylacetamide and acetone was 7:3) to obtain a solution. The solution was used as a spinning solution, and electrospinning was performed at a flow rate of 0.15 mL / h, a voltage of 14 kV and a receiving distance of 15 cm to obtain polysulfone fibers with an average diameter of 300 nm and an average length of 2 mm. By weight, 45 parts of epoxy resin (model E-51), 6 parts of acrylonitrile-styrene-acrylate terpolymer (model PW-957), 12 parts of polysulfone fiber, 0.7 parts of silane coupling agent, and 3 parts of acetone were mixed and stirred. 8 parts of m-phenylenediamine were added and mixed. The mixture was then sprayed onto glass fiber wool and cured at 80°C for 2 hours, followed by curing at 150°C for 2 hours to obtain high tensile strength glass wool (the mass of the adhesive is 6% of the mass of the glass fiber wool).
[0039] Example 6 The preparation method of high tensile strength glass wool includes the following steps: Polysulfone was dissolved in a mixed solvent of N,N-dimethylacetamide and acetone (volume ratio of N,N-dimethylacetamide to acetone was 7:3) to obtain a solution. Nano-zirconia (average particle size 45 nm) was added to the solution and dispersed evenly to obtain a dispersion. This dispersion was used as the spinning solution, and electrospinning was performed at a flow rate of 0.15 mL / h, a voltage of 14 kV, and a receiving distance of 15 cm to obtain polysulfone fibers with an average diameter of 300 nm and an average length of 2 mm. The mass of the nano-zirconia was 6% of the mass of the polysulfone. By weight, 45 parts of epoxy resin (model E-51), 6 parts of acrylonitrile-styrene-acrylate terpolymer (model PW-957), 12 parts of polysulfone fiber, 0.7 parts of silane coupling agent, and 3 parts of acetone were mixed and stirred. 8 parts of m-phenylenediamine were added and mixed. The mixture was then sprayed onto glass fiber wool and cured at 80°C for 2 hours, followed by curing at 150°C for 2 hours to obtain high tensile strength glass wool (the mass of the adhesive is 6% of the mass of the glass fiber wool).
[0040] Example 7 The preparation method of high tensile strength glass wool includes the following steps: Polysulfone was dissolved in a mixed solvent of N,N-dimethylacetamide and acetone (volume ratio of N,N-dimethylacetamide to acetone was 7:3) to obtain a solution. Nano-silica (average particle size 45 nm) was added to the solution and dispersed evenly to obtain a dispersion. The dispersion was used as a spinning solution, and electrospinning was performed at a flow rate of 0.15 mL / h, a voltage of 14 kV, and a receiving distance of 15 cm to obtain polysulfone fibers with an average diameter of 300 nm and an average length of 2 mm. The mass of nano-silica was 6% of the mass of polysulfone. By weight, 45 parts of epoxy resin (model E-51), 6 parts of acrylonitrile-styrene-acrylate terpolymer (model PW-957), 12 parts of polysulfone fiber, 0.7 parts of silane coupling agent, and 3 parts of acetone were mixed and stirred. 8 parts of m-phenylenediamine were added and mixed. The mixture was then sprayed onto glass fiber wool and cured at 80°C for 2 hours, followed by curing at 150°C for 2 hours to obtain high tensile strength glass wool (the mass of the adhesive is 6% of the mass of the glass fiber wool).
[0041] Example 8 The preparation method of high tensile strength glass wool includes the following steps: Polysulfone was dissolved in a mixed solvent of N,N-dimethylacetamide and acetone (volume ratio of N,N-dimethylacetamide to acetone was 7:3) to obtain a solution. Nano-titanium dioxide (average particle size 45 nm) was added to the solution and dispersed evenly to obtain a dispersion. The dispersion was used as a spinning solution, and electrospinning was performed at a flow rate of 0.15 mL / h, a voltage of 14 kV, and a receiving distance of 15 cm to obtain polysulfone fibers with an average diameter of 300 nm and an average length of 2 mm. The mass of nano-titanium dioxide was 6% of the mass of polysulfone. By weight, 45 parts of epoxy resin (model E-51), 6 parts of acrylonitrile-styrene-acrylate terpolymer (model PW-957), 12 parts of polysulfone fiber, 0.7 parts of silane coupling agent, and 3 parts of acetone were mixed and stirred. 8 parts of m-phenylenediamine were added and mixed. The mixture was then sprayed onto glass fiber wool and cured at 80°C for 2 hours, followed by curing at 150°C for 2 hours to obtain high tensile strength glass wool (the mass of the adhesive is 6% of the mass of the glass fiber wool).
[0042] Comparative Example 1 The preparation method of high tensile strength glass wool includes the following steps: Polysulfone was dissolved in a mixed solvent of N,N-dimethylacetamide and acetone (volume ratio of N,N-dimethylacetamide and acetone was 7:3) to obtain a solution. The solution was used as a spinning solution, and electrospinning was performed at a flow rate of 0.15 mL / h, a voltage of 14 kV and a receiving distance of 15 cm to obtain polysulfone fibers with an average diameter of 300 nm and an average length of 2 mm. By weight, 45 parts epoxy resin (model E-51), 12 parts polysulfone fiber, 0.7 parts silane coupling agent and 3 parts acetone were stirred and mixed, and 8 parts m-phenylenediamine were added and mixed. The mixture was sprayed onto glass fiber wool, cured at 80°C for 2 hours, and then cured at 150°C for 2 hours to obtain high tensile strength glass wool (the mass of the adhesive is 6% of the mass of the glass fiber wool).
[0043] Comparative Example 2 The preparation method of high tensile strength glass wool includes the following steps: By weight, 45 parts of epoxy resin (model E-51), 6 parts of acrylonitrile-styrene-acrylate terpolymer (model XC280G), 0.7 parts of silane coupling agent, and 3 parts of acetone were mixed and stirred. 8 parts of m-phenylenediamine were added and mixed. The mixture was then sprayed onto glass fiber wool and cured at 80°C for 2 hours, followed by curing at 150°C for 2 hours to obtain high tensile strength glass wool (the mass of the adhesive is 6% of the mass of the glass fiber wool).
[0044] Comparative Example 3 The preparation method of high tensile strength glass wool includes the following steps: By weight, 45 parts of epoxy resin (model E-51), 0.7 parts of silane coupling agent and 3 parts of acetone were stirred and mixed, and 8 parts of m-phenylenediamine were added and mixed. The mixture was then sprayed onto glass fiber wool, cured at 80°C for 2 hours, and then cured at 150°C for 2 hours to obtain high tensile strength glass wool (the mass of the adhesive is 6% of the mass of the glass fiber wool).
[0045] Performance testing The tensile strength perpendicular to the surface of glass wool samples (100 mm thick) was determined using the method in GB / T25975-2018 "Rock Wool Products for External Thermal Insulation of Building Walls". The performance results of each embodiment and comparative example are shown in Table 1.
[0046] Table 1 Tensile strength test results
[0047] As can be seen from the tensile strength test data in Table 1, the tensile strength of all the sample samples in the examples was significantly higher than that of the three comparative examples. The blank comparative example 3, which only used pure epoxy resin adhesive, had a tensile strength of only 40.3 kPa. The tensile strength of comparative example 1, which only added polysulfone fiber, was 49.2 kPa. The tensile strength of comparative example 2, which only added acrylonitrile-styrene-acrylate terpolymer, was 45.0 kPa. However, the tensile strength of examples 1 to 4, which combined terpolymer and polysulfone fiber, all reached more than 53.6 kPa. This proves that there is a significant synergistic reinforcing effect between acrylonitrile-styrene-acrylate terpolymer and polysulfone fiber. The combination of the two can greatly improve the tensile properties of glass wool. The comparison results of different types of terpolymers showed that the PW-957 model in Example 5 had the best improvement effect. The tensile strength of Example 6, which was combined with nano-zirconia modified polysulfone fiber, reached 64.0 kPa, which was higher than that of Examples 7 and 8, which were modified polysulfone fiber with nano-silica and nano-titanium dioxide. This confirmed that nano-zirconia can better strengthen the strength of polysulfone fiber itself compared with conventional inorganic nanofillers, and further improve the tensile properties of the product.
[0048] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high tensile strength glass wool, characterized in that, The components include glass fiber cotton and an adhesive, wherein the adhesive comprises the following raw materials in parts by weight: 40-45 parts epoxy resin, 4-6 parts acrylonitrile-styrene-acrylate terpolymer, 5-12 parts polysulfone fiber, 4-8 parts curing agent, 1-3 parts diluent, and 0.5-0.8 parts silane coupling agent.
2. The high tensile strength glass wool according to claim 1, characterized in that, The acrylonitrile-styrene-acrylate terpolymer includes at least one of XC280G, PW-957, S210B, and WX-9951UV.
3. The high tensile strength glass wool according to claim 1, characterized in that, The polysulfone fiber has an average diameter of 200~300nm and an average length of 1~2mm.
4. The high tensile strength glass wool according to claim 3, characterized in that, The method for preparing the polysulfone fiber includes the following steps: dissolving polysulfone in a solvent to obtain a solution; using the solution as a spinning solution, electrospinning is performed to obtain the polysulfone fiber.
5. The high tensile strength glass wool according to claim 3, characterized in that, The method for preparing the polysulfone fiber includes the following steps: dissolving polysulfone in a solvent to obtain a solution; adding nano-zirconia to the solution and dispersing it evenly to obtain a dispersion; and using the dispersion as a spinning solution to obtain the polysulfone fiber through electrospinning.
6. A high tensile strength glass wool according to claim 4 or 5, characterized in that, The mass-to-volume ratio of the polysulfone to the solvent is 1 g: 6~12 mL.
7. A high tensile strength glass wool according to claim 4 or 5, characterized in that, The electrospinning voltage is 10~14kV, the receiving distance is 10~15cm, and the flow rate of the spinning solution is 0.15~0.30mL / h.
8. The high tensile strength glass wool according to claim 5, characterized in that, The mass of the nano-zirconia is 5% to 8% of the mass of the polysulfone.
9. The high tensile strength glass wool according to claim 1, characterized in that, The mass of the adhesive is 6% to 10% of the mass of the glass fiber cotton.
10. A method for preparing high tensile strength glass wool, used to prepare the high tensile strength glass wool according to any one of claims 1 to 9, characterized in that, Includes the following steps: Epoxy resin, acrylonitrile-styrene-acrylate terpolymer, polysulfone fiber and diluent are stirred and mixed, curing agent is added and mixed, and the mixture is sprayed onto glass fiber wool and cured to obtain the high tensile strength glass wool.